Optimization of organic tandem solar cells based on small molecules - Riede, M; Uhrich, C; Timmreck, R; Widmer, J; Wynands, D; Levichkova, M; Furno, M; Schwartz, G; Gnehr, W; Pfeiffer, M; Leo, K (Institute of Electrical and Electronics Engineers, 2010)
Organic solar cells (OSC) have attracted growing attention in recent years and their development has reached a stage at which several companies are preparing to make them commercially available either as standalone products or integrated into other device. There are different production routes for OSC: one very promising approach uses thermal evaporation of small organic molecules in vacuum, i.e. the same approach that is used in all current commercial manufacturing of organic LEDs. We use vacuum processing to create an organic stack in the p-i-n concept. In this concept the intrinsic absorber layers are sandwiched between p- and n-doped wide gap transport layers which leads to a nearly ideal solar cell structure and offers a stable platform both for investigation of fundamental processes and device optimization. In recent years it was found that the device operation crucially depends on the morphology of the bulk heterojunction and that optical interference effects in the organic stack play an important role for light absorption. We show here how the morphology of the organic layers can be controlled in vacuum deposited layers, and describe the optical optimization of tandem solar cells, for which an efficient recombination contact and current matching are essential requirements. Applying these principles and subsequently combining two complementary absorbing subcells lead to a tandem organic solar cell with an independently certified efficiency of 6.07% on 2cm2 device area, i.e. the first OSC over 6% on module relevant dimensions. © 2010 IEEE.